A case of percutaneous mitral balloon valvuloplasty complicated by pericardial effusion and thrombus formation on the interatrial septum - İsa Öner Yüksel; Selçuk Küçükseymen; Göksel Çağırcı; Şakir Arslan (KARE Publishing, 2014)
Percutaneous mitral balloon valvuloplasty (PMBV) is the primary treatment in mitral stenosis patients with appropriate valve anatomy with no contraindications present. Pericardial effusion, cardiac tamponade and thrombus formation are rare but serious complications of this procedure. In the literature, the mortality rate associated with PMBV has been reported as 1%. The presence of intracardiac thrombus is a contraindication for PMBV. However, thrombus formation during the process is a very rare condition. In this case, we present a patient with rheumatic mitral stenosis, with both pericardial effusion and intracardiac thrombus, after laseration at the base of the left atrium during the valvuloplasty procedure.